Penerapan Program Aksara Lontara dan MS Office untuk Menerjemahkan Al-Quran ke dalam Bahasa Bugis di Pesantren As'adiyah, Kabupaten Wajo - Faridah Rahman; Yusring Sanusi Baso; Andi Agussalim; Najmuddin H. Abd. Safa; Supratman Supratman (Universitas Hasanuddin, 2020)
Study Program of Arabic of Hasanuddin University conducted community services at the As'adiyah Islamic Boarding School in Sengkang, Wajo Regency, South Sulawesi, Indonesia. The activity trained the teachers of the boarding school using the Lontara script application in translating the Holy Qur'an into Buginese. Also, this activity provided technical skills in using MS Word in writing articles for the teachers. Arabic Study Program used Cooperative and Collaborative Learning methods to train participants. Five lecturers from Arabic Study Program became facilitators in this activity.Meanwhile, the number of participants involved in this activity was 45 teachers. Besides, at the beginning of the event, this activity was also attended by 50 students of the Ma'had Aly Sengkang As'adiyah Islamic Boarding School. The results of this community Service are a sample translation of the Holy Quran that is the Surah Al-Fatihah and the Surah Al-Ikhlas into the Buginese. The participants translated the Holy Quran into Buginese using in Lontara script.